Early Initiation of Anticoagulation Improves the Long-Term Prognosis in Patients With Antiphospholipid Syndrome Associated Portal Vein Thrombosis - You, Hanxiao; Zhao, Jiuliang; Huang, Can; Tian, Xinping; Li, Mengtao; Zeng, Xiaofeng (Frontiers in Medicine, 2021)
Objectives: Portal vein thrombosis (PVT) is a rare and severe clinical phenotype of antiphospholipid syndrome (APS) with a poor prognosis. Anticoagulation therapy is efficient but is associated with potentially severe bleeding episodes, especially for those patients with thrombocytopenia. We conducted this case-control study to explore the clinical features and associated factors of PVT in APS patients, the re-canalization rate of the PVT after anticoagulation and investigate the beneficial effects of early initiation of anticoagulation in patients with APS associated PVT. Methods: We enrolled patients with APS associated PVT as the case group, and age-, and entry-time-matched APS patients without PVT (1:2) as the control group. We explored the associated factors of PVT in APS patients using multivariate logistic regression analysis. The re-canalization rate of the PVT after anticoagulation was analyzed using the survival analysis. Results: A total of 34 patients (8 males and 26 females) with APS-PVT were enrolled, with a median follow-up time of 3 years (1.5, 7 years). Multivariate logistic regression analysis showed that thrombocytopenia (OR 6.4, 95%CI 1.561–26.218, P = 0.01), hypersensitive c-reactive protein >3 mg/L (OR 4.57, 95%CI 1.426–14.666, P = 0.011), anti β2GPI positive (OR 5, 95%CI 1.816–13.772, P = 0.002) and aPL double-positive (OR 4.08, 95%CI 1.312–12.429, P = 0.013) were independent associated factors for PVT in APS. Survival analysis revealed that effective anticoagulation could increase re-canalization rate significantly (log-rank p = 0.001), with better prognosis (lower mortality rate, log-rank p = 0.045). Conclusions: PVT could be the first presentation of APS with insidious onset and atypical clinical symptoms and easily be misdiagnosed. For patients with APS, double aPLs positive, thrombocytopenia, and inflammation could be the associated factors of PVT. Early diagnosis and anticoagulation treatment can bring thrombus re-canalization thereby significantly improving the prognosis.